Social Behaviour and Settlement Structure: Preliminary Results of a Distribution Analysis on Sites of the Maglemose Culture - Grøn, Ole (Journal of Danish Archaeology, 1983)
Social Behaviour and Settlement Structure. Preliminary Results of a Distribution Analysis on Sites of the Maglemose Culture.